Pengaruh kepemimpinan dan konflik kerja terhadap produktivitas karyawan PT. Cahaya Murni Pakanindo Pekanbaru - Setiawan, Dila Agustha; Sasmita, Jumiati; Amsal, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the variables influence the leadership and conflict work simultaneously and significantly affect the productivity of employees of PT. Pure light Pakanido Pekanbaru.As for the population in this study were all employees of PT. Pure light Pakanindo Pekanbaru totaling 117 people consisting of various parts and the whole population sampled in this study using census sampling method. Analysis of the data used is descriptive analysis, as it also uses the quantitative analysis using multiple linear regression with SPSS version 17.0.From the results of the testing that has been done, simultaneous regression test (F-test) showed that the leadership and work conflicts simultaneously significant effect on employee productivity. Partial Test results (t test) showed that the variables of leadership partially significant effect on labor productivity, and workplace conflict variables partially significant effect on employee productivity.Keywords : leadership, workplace conflict and employee productivity.